PERAN SENIMAN BANYUMAS DALAM PELESTARIAN CALUNG BANYUMASAN: STUDI KASUS PADA SENIMAN SUJIMAN BAWOR - Suharto, Suharto (Indonesian Journal of Conservation, 2018)
This study aims to describe the role of an artist Calung Banyumasan who has a high dedication in maintaining two roles at once namely maintaining the economic life of his family, the traditions he loves and his responsibilities as a member of the community. This research uses a hermenuetic approach, integrated professional theory, and compensation theory to reveal the attitude of an artist who performs the attitude taken in his social cultural life. The results of the study show that artists who love art and culture will maintain their attitude by performing their faith. This activity can be in the form of working as an artist earnestly, doing other work as a support for his life and carrying out his social activities as a gesture of attitude that is in love with the art and culture of the ancestors he loves.